2017
DOI: 10.4103/0366-6999.211539
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Mutation in Peripheral Myelin Protein-22 Causes Charcot-Marie-Tooth Disease

Abstract: Background:Charcot-Marie-Tooth disease (CMT) is the most common inherited peripheral neuropathy. A great number of causative genes have been described in CMT, and among them, the heterozygous duplication of peripheral myelin protein-22 (PMP22) is the major cause. Although the missense mutation in PMP22 is rarely reported, it has been demonstrated to be associated with CMT. This study described a novel missense mutation of PMP22 in a Chinese family with CMT phenotype.Methods:Targeted next-generation sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…One hundred and fifty unrelated CMT patients consisting of 96 males and 54 females were recruited from Second Affiliated Hospital of Zhejiang University School of Medicine and Huashan Hospital of Fudan University between December 2007 and August 2018. Patients were evaluated and diagnosed by at least two senior neurologists according to the strategy described in our previous reports . This study was approved by the local Ethics Committees for medical research.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred and fifty unrelated CMT patients consisting of 96 males and 54 females were recruited from Second Affiliated Hospital of Zhejiang University School of Medicine and Huashan Hospital of Fudan University between December 2007 and August 2018. Patients were evaluated and diagnosed by at least two senior neurologists according to the strategy described in our previous reports . This study was approved by the local Ethics Committees for medical research.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Owing to CMT's clinical and genetic heterogeneity, it is expensive and time-consuming to screen all the possible causative genes using conventional Sanger sequencing. However, highthroughput targeted next-generation sequencing (NGS) has been employed successfully in CMT 9,10 and other neurogenetic diseases such as amyotrophic lateral sclerosis (ALS), [11][12][13] hereditary spastic paraplegia (HSP), 14,15 and hereditary ataxia (HA). 16,17 Consequently, nearly 90 genes associated with CMT and other inherited peripheral neuropathies have been assembled in a gene panel, and parallel sequencing can be performed to interrogate these genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Researching the relation between sequence and structure in protein has the great scienti c interest [18], and we can use the sequences to explore the protein evolution and function [19,20]. Studies reported that the missense mutations caused by the sequence variations were related to the protein function to account for the phenotype variations [21][22][23][24]. Here, we identi ed a missense mutation (g.17303383G > T), and it changed the protein secondary structure by prediction with the SOPMA.…”
Section: Discussionmentioning
confidence: 98%
“…[ 5 6 7 ] The clinical features of PMP2 -associated neuropathy were similar to PMP22 duplication. [ 6 8 ] BSCL2 pathogenic variants were originally identified in patients with AR congenital generalized lipodystrophy type 2 and were subsequently found to cause a broad spectrum of neurological disorders. [ 9 ] The BSCL2 pathogenic variant p.S90W was identified to cause AD-CMT2 in a Korean family, who presented predominant thenar muscle atrophy, frequent sensory disturbances, and pyramidal tract signs.…”
Section: Introductionmentioning
confidence: 99%